2017
DOI: 10.1515/abm-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Paid maternity leave extension and exclusive breastfeeding practice: evidence from Brunei

Abstract: BackgroundExclusive breastfeeding (EBF) of infants in their first 6 months postpartum is beneficial. However, maternal employment and short maternity leave impede EBF practice. In 2011, Brunei implemented a new Maternity Leave Regulation to extend paid maternity leave.ObjectivesTo compare the prevalence of EBF between employed and nonworking mothers in Brunei, before and after extending paid maternity leave, to determine its effect on EBF and to determine the effects of maternal and infant sociodemographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…This, in turn, may help to avert some of the associated premature child mortality and cognitive losses [5, 40, 41]. A potential impact of an insufficient length of paid maternity leave is that it limits the possibility of providing breastfeeding according to recommendation [3, 5, 42]. If the paid maternity leave policy is implemented optimally and increased to 6 months of leave, the number of deaths averted may be large.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, may help to avert some of the associated premature child mortality and cognitive losses [5, 40, 41]. A potential impact of an insufficient length of paid maternity leave is that it limits the possibility of providing breastfeeding according to recommendation [3, 5, 42]. If the paid maternity leave policy is implemented optimally and increased to 6 months of leave, the number of deaths averted may be large.…”
Section: Discussionmentioning
confidence: 99%
“…Alhaji et al have reported in this issue a study of the outcomes of paid maternity leave on the maintenance of exclusive breastfeeding in Brunei [11]. Implementing a new maternity leave regulation to extend paid maternity leave in Brunei (effective January 2011) moderately increased exclusive breastfeeding at 6 months of infant age by 12 percentage points, from 29% in 2010 to 41% in 2013.…”
Section: Initiation and Maintenance Of Breastfeeding: The Need For Esmentioning
confidence: 99%
“…Implementing a new maternity leave regulation to extend paid maternity leave in Brunei (effective January 2011) moderately increased exclusive breastfeeding at 6 months of infant age by 12 percentage points, from 29% in 2010 to 41% in 2013. The increase was seen in both mothers employed by the government and those employed in the private sector [11]. However, paid maternity leave alone is not sufficient to effect change in exclusive breastfeeding practice, particularly for primiparous mothers, mothers with male infants, and other subgroups such as those with sore nipples and erroneous perception of inadequate milk supply and therefore not meeting the needs of their infants [12,13].…”
Section: Initiation and Maintenance Of Breastfeeding: The Need For Esmentioning
confidence: 99%